2020
DOI: 10.17138/tgft(8)153-157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <i>Asystasia gangetica</i> as a potential forage in terms of growth, yield and nutrient concentration at different harvest ages

Abstract: The objective of this experiment was to analyze growth dynamics, yield and nutrient concentration of Asystasia gangetica (L.) T. Anderson at different harvest ages. A pot experiment was conducted at Green House Laboratory of Agrostology, Faculty of Animal Science, Bogor Agricultural University, Indonesia, during the growing season of 2018. Seedlings were transplanted into 115 polybags arranged in a completely randomized design with 23 replications. Plant height, number of leaves, number of branches, dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Three weeks A. gangetica seedlings with 4 leaves were transplanted into 12 x 12 cm pots, stored in a greenhouse (Kumalasari et al 2020), and acclimatized for 1 week. Each pot was filled with 80 g of planting medium and planted with one seedling.…”
Section: Seedling Growthmentioning
confidence: 99%
“…Three weeks A. gangetica seedlings with 4 leaves were transplanted into 12 x 12 cm pots, stored in a greenhouse (Kumalasari et al 2020), and acclimatized for 1 week. Each pot was filled with 80 g of planting medium and planted with one seedling.…”
Section: Seedling Growthmentioning
confidence: 99%
“…A. gangetica telah digunakan di berbagai wilayah sebagai pakan ternak, seperti Riau (Ramdani et al 2017), Batanghari (Adriadi et al 2012) termasuk di wilayah Asia (Norlindawati et al 2019) dan Afrika (Adigun et al 2014). Menurut Kumalasari et al (2020b), A. gangetica memiliki kandungan nutrien yang baik sebagai pakan ternak, terutama daunnya dengan kandungan protein kasar mencapai 24,2%.…”
Section: Pendahuluanunclassified
“…Pada daerah yang ternaungi seperti daerah perkebunan dengan tanaman yang relatif tinggi, tanaman ini dapat menghasilkan daun dan menghasilkan organ vegetatif sehingga memiliki pertumbuhan yang cepat dan kompetitif serta sering kali digunakan sebagai pakan ternak ruminansia (Junaidi & Sawen 2010). Daun A. gangetica memiliki kandungan nutrien yang lebih tinggi dibandingkan bagian batang (Kumalasari et al 2020b), oleh karena itu penting dilakukan penelitian mengenai keragaman morfologi tumbuhan A. gengetica di berbagai wilayah untuk mengetahui produktivitas dan kualitas A. gangetica pada lingkungan yang berbeda.…”
Section: Pendahuluanunclassified
“…(c) It is easy to grow and at a fast growth rate [10]. Under experimental polybags in greenhouse conditions, Kumalasari et al [11] reported that the dry matter yields of both the leaf and stem of A. gangetica increased (p < 0.001) progressively with age and reached 11.6 g leaf dry matter, 19.0 g stem dry matter/plant, and 30.6 g total dry matter/plant at 90 days after transplanting. Even though the biomass is not substantial when compared with other plants, the fast growth rate of the weeds can still justify A. gangetica as a phytoremediator of PTMs.…”
Section: Introductionmentioning
confidence: 99%